Defect on high rise government office buildings in Kelantan / Abdullah Daud and Mohd Fisal Ishak - Daud, Abdullah; Ishak, Mohd Fisal (2018)
Malaysia is one of the developing countries where many projects are being implemented especially in the construction industry. The construction industry is getting more modern, advanced and growing day by day. Despite that, problems such as building defects still occur. Defect is sometimes used as synonym with failure but the preferred meaning is to indicate only a deviation from some standard that may, but will not necessarily, result in failure. There are many types of defects that can be found in the construction industry in Malaysia. The types of defect can be grouped by the element such as external wall, internal wall, column, door, window, roof, ceiling, floor, and others. The aim of this is study to investigate the causes and effects of defect on high rise government office buildings in Kelantan. This study uses questionnaires to collect data from the respondents. The result shows that the majority of respondents agreed that crack is the most occurring type of defect in government office buildings in Kelantan. Amongst the main reasons that causes defects are poor workmanship and poor maintenance. This creates dissatisfaction to occupants in the building and affects their productivity and performance. As a conclusion, it is imperative that the personnel who are in charge of the maintenance of these buildings should take precaution to ensure that these defects could be minimized.